A High‐Performance Lithium‐Ion Capacitor Based on 2D Nanosheet Materials. Issue 6 (28th November 2016) - Li, Shaohui; Chen, Jingwei; Cui, Mengqi; Cai, Guofa; Wang, Jiangxin; Cui, Peng; Gong, Xuefei; Lee, Pooi See
Abstract : Lithium‐ion capacitors (LICs) are promising electrical energy storage systems for mid‐to‐large‐scale applications due to the high energy and large power output without sacrificing long cycle stability. However, due to the different energy storage mechanisms between anode and cathode, the energy densities of LICs often degrade noticeably at high power density, because of the sluggish kinetics limitation at the battery‐type anode side. Herein, a high‐performance LIC by well‐defined ZnMn2 O4 ‐graphene hybrid nanosheets anode and N‐doped carbon nanosheets cathode is presented. The 2D nanomaterials offer high specific surface areas in favor of a fast ion transport and storage with shortened ion diffusion length, enabling fast charge and discharge. The fabricated LIC delivers a high specific energy of 202.8 Wh kg −1 at specific power of 180 W kg −1, and the specific energy remains 98 Wh kg −1 even when the specific power achieves as high as 21 kW kg −1 . Abstract : A high‐performance lithium‐ion capacitor is fabricated using well‐defined ZnMn2 O4 ‐graphene hybrid nanosheets anode and N‐doped carbon nanosheets cathode. Owing to the large surface areas of 2D nanostructures for ion transport and storage with shortened ion diffusion length, the full device exhibits both excellent energy and power density.